COMPLEMENTARY AND INTEGRATIVE PRACTICES IN PRIMARY HEALTH CARE - Pollyane da Costa Matos; Carolina Rodrigues Laverde; Priscila Gomes Martins; Juliana Martins de Souza; Nunila Ferreira de Oliveira; Calíope Pilger (Universidade Federal do Paraná, 2018)
Objective: to analyze the knowledge and perceptions of nurses working in Primary Health Care in a municipality of Southeastern Goiás on Complementary and Integrative Practices. Method: a descriptive and exploratory study with a qualitative approach, with nurses who have been working for more than 6 months in Primary Health Care. Data was collected by semi-structured interviews in 2015 and submitted to thematic content analysis. Results:three categories emerged: I - Nurses' knowledge about Complementary and Integrative Health Practices, difficulty in conceptualizing these practices and perception as a complementary treatment; II - Challenges and difficulties in implementing Complementary and Integrative Health Practices in Primary Health Care; III - Complementary and Integrative Health Practices as a tool for self-care and promotion of quality of life. Conclusion: Training on the use of these practices as a resource of care is necessary at graduation and in continuing education.